An armorial shield for two queens. A Heraldical binding of the National Library of Spain - de Francisco Olmos, José María (Revista General de Información y Documentación, 2019)
This work highlights the possibilities of a very specific heraldic source, book bindings, which were especially important between the sixteenth and nineteenth centuries, and that can show us numerous heraldic variants, and specifically the representation in them of the queens of Spain during the first half of the 18th century and the study, identification and dating of a heraldic binding with the shields of two queens of Spain, María Amalia de Sajonia and Isabel de Farnesio